Squamous Cell Carcinoma in Chinese Hamsters (Cricetulus griseus) - Conceição, Alexsandro Machado; de Andrade, Rachel Livingstone Felizola Soares; Sarmento, Carlos Alberto Palmeira; Souza, Karine dos Santos; Fioretto, Emerson Ticona (Acta Scientiae Veterinariae, 2018)
Background: The companion animal market has changed over the years. The number of people living in small apartments has increased; as a result, the demand for small pets such as exotics, fish, and small rodents has also increased due to their smaller space requirements and ease of handling and care. Pets help relieve anxiety and stress in people suffering from social issues. Small rodents are usually bred in specific cages with cellulose or wood shaving bedding, and fed with commercially available diets. Small rodent clinics struggle due to the lack of scientific reports on some diseases and therapies. To date, the oncology literature is too limited to develop better diagnosis and treatment methods. Here, we report three cases of squamous cell carcinoma in the mandibular region of Chinese hamsters (Cricetulus griseus). Case: Three adult male hamsters averaging 1.5 years old, from different pet stores, bred under home conditions by different owners in Sergipe, Brazil, were brought to the Dr. Vicente Borelli Hospital at Pio X University for exotic veterinary care. Each animal had been bred alone in a specific breeding cage. Each had a history of apathy, loss of appetite, and rapid deformity of the facial region. Radiographs showed areas of bone involvement and extensive injury, with partial resorption of the left ramus and angle of the mandibular region. Due to the location of the tumor mass, the clinical status, and limitations in systemic treatment, euthanasia was recommended for each animal. After anamnesis, the animals were subjected to clinical assessment. A firm and well-circumscribed mass was identified on palpation. In case A, it compromised the left mandible from the angle to the body and extended to the maxillary soft tissues and left superior lips. In case B, it extended from the ramus to the symphysis on the left side and to the maxillary region, similar to case A. In case C, it extended on both sides of the mandible symphysis, with no alterations in the maxillary soft tissues. Following clinical examination, each animal underwent laterolateral and dorsoventral radiographic examination; no images were suggestive of pulmonary metastasis. However, an expansive mandibular lesion with partial resorption, suggestive of bone neoplasia, was detected. The animals were dehydrated and in clinical distress, and euthanasia was recommended. Histopathological examination of samples from the tumor sites revealed moderate cellular and nuclear pleomorphism and proliferation of neoplastic keratinocytes, suggestive of squamous cell carcinoma, a malignant tumor of epidermal keratinocytes with a highly invasive and aggressive nature. Discussion: The number of reports in the literature of cancer in small rodent companion animals has lead us to believe that neoplasms in these animals are misdiagnosed and/or that their prevalence is underreported. The literature describes that the tumor incidence in hamsters is 3-40%, and that the incidence is higher in male rodents. This incidence range increases the analysis of cancer in these animals from rare to middle-frequent what do not contribute to the animals’ clinics and to small rodent therapeutics. Differential diagnosis of squamous cell carcinoma and other tumor types should be addressed, especially osteosarcomas. Histopathological examination is essential to clarify the etiopathogenesis. Keywords: rodents, neoplasm, keratinocytes.